Text-Speech Modeling of Addressee of Advertising Training Courses - S. N. Vinogradov; V. B. Shavlyuk (Научный диалог)
The image of the target audience of training courses advertising is considered. The authors set a goal — to characterize the speech modeling of the addressee of advertisement on the basis of advertising discourse. The object of the study is the private discourse of Spanish courses advertising, the subject of the study is the language and speech units of the advertising text, which create a psychological and speech portrait of the addressee of the advertisement. The novelty of the study is seen in the fact that, on the basis of advertising texts, the communicative features of not their authors, but their addressees are analyzed. The relevance of the study is due to the importance of advertising discourse in modern mass culture, in particular, the interest in its influencing function. The authors dwell on the properties of the advertising text as one of the targeting tools, which is carried out due to the positive tone created by the system of language and speech units. The most active language and speech means of creating a positive tone in the text of advertising training courses are analyzed. Particular attention is paid to the vocabulary of different thematic groups. The authors conclude that the lexical composition of advertising training courses makes it possible to reconstruct fragments of the psychological and speech portrait of advertising recipients (students), to model their psychological characteristics, their range of interests and preferences.